Analisis Layanan Perpustakaan - KMS Badaruddin (Jambura Journal of Educational Management, 2023)
This article is entitled "Analysis of School Library Services at SMA Negeri 1 Tanjung Lago". This study aims to determine the school library services and the constraints of school library services at SMA Negeri 1 Tanjung Lago. The problems that occur are related to library services where the current needs of the library have not been met, this is what causes library services to not run fully. In this research, the type of research used is the type of field research that is qualitative. In the study, informants were also the head of the library, library staff, deputy head of curriculum, and students. Data collection techniques used are data reduction, data presentation, and drawing conclusions. Based on the results of the discussion, it can be concluded that school library services are carried out through activities (1) reading room services, in the library of SMA Negeri 1 Tanjung Lago the reading room services are quite good, with the provision of facilities in the form of tables, chairs, air circulation, and room lighting. (2) circulation service, for this service is not maximized because it is still done manually. (3) reference service, where this service is not maximized, because there are still limited collections of books, and there are still many collections of old books. (4) information and communication technology services, this service has not been implemented, due to limited supporting facilities and the lack of library staff in the field of expertise. It can be concluded that the school library services at SMA Negeri 1 Tanjung Lago have not run optimally in accordance with national library standards.